2011
DOI: 10.1038/modpathol.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear overexpression of lymphoid-enhancer-binding factor 1 identifies chronic lymphocytic leukemia/small lymphocytic lymphoma in small B-cell lymphomas

Abstract: Lymphoid-enhancer-binding factor 1 (LEF1), coupling with b-catenin, functions as a key nuclear mediator of WNT/b-catenin signaling, which regulates cell proliferation and survival. LEF1 has an important role in lymphopoiesis, and is normally expressed in T and pro-B cells but not mature B cells. However, gene expression profiling demonstrates overexpression of LEF1 in chronic lymphocytic leukemia, and knockdown of LEF1 decreases the survival of the leukemic cells. So far, the data on LEF1 expression in B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 31 publications
2
42
3
1
Order By: Relevance
“…The Wnt/β-catenin pathway plays an important role in the progression of leukemia, myeloma (16)(17)(18)(19) and several subtypes of lymphoma, such as Epstein-Barr virus (EBV)-positive Burkitt's lymphoma (BL) (20)(21)(22), mantle cell lymphoma (MCL) (23)(24)(25), cutaneous lymphoma (26), extranodal marginal zone lymphoma (27), ALK-positive anaplastic large cell lymphoma (28), small B-cell lymphoma (29) and DLBCL (9,30). Scientists demonstrated that ethacrynic acid (EA) and the antifungal agent ciclopirox olamine (cic) inhibited the Wnt/β-catenin signaling in OPM-2 myeloma and three lymphoma cell lines (OCI-LY8-LAM-53, SU-DHL-4 and Raji) in vitro, leading to apoptosis and a significant decrease in the viability of lymphoma and its cell lines (30).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway plays an important role in the progression of leukemia, myeloma (16)(17)(18)(19) and several subtypes of lymphoma, such as Epstein-Barr virus (EBV)-positive Burkitt's lymphoma (BL) (20)(21)(22), mantle cell lymphoma (MCL) (23)(24)(25), cutaneous lymphoma (26), extranodal marginal zone lymphoma (27), ALK-positive anaplastic large cell lymphoma (28), small B-cell lymphoma (29) and DLBCL (9,30). Scientists demonstrated that ethacrynic acid (EA) and the antifungal agent ciclopirox olamine (cic) inhibited the Wnt/β-catenin signaling in OPM-2 myeloma and three lymphoma cell lines (OCI-LY8-LAM-53, SU-DHL-4 and Raji) in vitro, leading to apoptosis and a significant decrease in the viability of lymphoma and its cell lines (30).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicated that INPP5F and LEF1 may have a role in the therapeutic strategies of CLL [22,23] . More potential connections between these genes and B-CLL could be identified from the B-CLL_ Meta database (see B-CLL_Meta → NRIP1, INPP5F and LEF1), which is available in the open source 'Bioinformatics Database' (http://database.gousinfo.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analyses were successful in case 1, 46XX,t(2;6)(p11.2;p25) [10]/46XX,t(1;11)(q21;q23) [1]/46XX [9], and case 3, 4 6 X Y, t ( 2 ; 6 ) ( p 1 2 ; p 2 5 ) [ 1 ] / 4 6 , s l , -Y, -4 , -8 , -9 , -9,add(11)(q23),+5mar[1]/46XY [11]. No evidence of rearrangement in BCL2, BCL6, MYC, and CCND1 was obtained in the present cases, whereas in previous cases, 2 2 The present and previous findings indicate that IRF4 rearrangement may be related to the development of low-grade and primary high-grade lymphomas and that some IRF4-rearranged low-grade lymphomas may progress to high-grade lymphomas.…”
Section: Admixed T Cells and Tissue Scarcity The Immunohistochemicalmentioning
confidence: 99%